Blue Cone Monochromatism: A Case Report with Opsoclonus and Light Exposure - Llorente-La-Orden, Carlos; Burgos-Blasco, Bárbara; Domingo-Gordo, Blanca; Hernández-García, Elena; Gómez-de-Liaño, Rosario (Journal of Pediatric Genetics, 2020)
Blue cone monochromatism (BCM) is a rare X-linked congenital vision disorder that is characterized by a cone dysfunction. We present a case of a 3-year-old boy referred to our department with abnormal eye movements since birth, impaired vision, and difficulties in distinguishing colors. A tendency to stare at the sun was noted. Examination revealed severe loss of visual acuity, high myopia, and opsoclonus. A mutation screening of OPN1LW/OPN1MW gene cluster was performed showing a nucleotide substitution encoding a Cys203Arg (C203R) missense mutation. The diagnosis of BCM in this case was clear and the patient harbored the most frequent genetic alteration. Opsoclonus and continued voluntary light exposure are novel features that have not been previously reported in BCM.
Keywords: monochromatism; opsoclonus; cones